Анализ методов измерения дальности связи между датчиками беспроводной сенсорной сети - Куля, Ю. Э.; Герус, М. А.; Панчук, О. Р.; Борисенко, Л. А.; Красюкова, В. В. (ХНУРЕ, 2019)
Wireless sensor networks (WSNs) are often used to collecting information from a variety of sensors placed on a given territory. In some applications it is required to know the coordinates of the sensor, from which received a certain signal. It becomes a challenge if when installing the sensors it was not possible to accurately measure their coordinates or either the sensors were mounted on mo-bile objects. In such cases, the problem arises of quickly determining the coordinates of a node. As a result, two methods for measur-ing the coordinates and communication distances between wireless nodes, RSSI and ToF, were developed for the WSN.
Keywords: WSN; IEEE 802.15.4; RSSI; безпроводная сенсорна сеть; ToF